The role of radio frequency scattering in high-energy electron losses from minimum-B ECR ion source. (12th February 2021) - Izotov, I V; Shalashov, A G; Skalyga, V A; Gospodchikov, E D; Tarvainen, O; Mironov, V E; Koivisto, H; Kronholm, R; Toivanen, V; Bhaskar, B
Abstract: The measurement of the axially lost electron energy distribution escaping from a minimum- B electron cyclotron resonance ion source in the range of 4–800 keV is reported. The experiments have revealed the existence of a hump at 150–300 keV energy, containing up to 15% of the lost electrons and carrying up to 30% of the measured energy losses. The mean energy of the hump is independent of the microwave power, frequency and neutral gas pressure but increases with the magnetic field strength, most importantly with the value of the minimum- B field. Experiments in pulsed operation mode have indicated the presence of the hump only when microwave power is applied, confirming that the origin of the hump is radio-frequency-induced momentum space diffusion. A possible mechanism of the hump formation is considered based on the quasi-linear model of plasma–wave interaction.